GEOCHEMISTRY AND CONDITIONS OF FORMATION OF THE SOLGON GRANITOID BATHOLITH (KUZNETSK ALATAU) - Grebenshchikova V.I.; Maksimchuk Yu.V. (My University, 2003)
Under consideration is the geological and geochemical signature of the granitoid rocks (from gabbro to leucogranite) making up a large Early Paleozoic batholith of the Kuznetsk Alatau. The early (progressive) stage of batholith formation was due to magmatic replacement and partial melting of the metabasite crust under the effect of a subalkalic mantle-derived magma. The rocks formed at this stage are exocontact hornfelses and endocontact hybrid diorites and monzonites of hybrid habit. The transitions between these rocks are illustratively displayed in the pattern of distribution of rare-earth elements. The next (regressive) stage was due to the differentiation of a monzonitoid melt and its crystallization, which proceeded against the background of a considerable decrease in alkalinity of the residual melt and led to the formation of the main facies rock variety - granodiorite-tonalite. It is characterized by higher contents of Ba, Sr, B, and IGE, lower contents of K, Li, Rb, and Cs, and very low concentrations of Be, Sn, W, Nb, and Ta as compared with palyngenetic granitoids of other regions. The granitic magma was generated in a separate chamber and was not produced by differentiation of a granodiorite melt. In composition, the formed hornblende-biotite granites are close to trondhjemites (Na/K>1). A small volume of the residual melt formed during the fractionation of the granitic magma appeared in the stocks and dikes of subalkalic leucogranites. The presence of postbatholith dikes of basic and intermediate compositions and their closeness in composition to monzonitoid rocks of batholith suggest that a deep-seated source of magma (and heat) had existed for a long time. The postbatholith dikes of quartz porphyries (ongonites) are characterized by higher, as compared with the other rocks of the batholith, contents of rare ore elements (Rb, Be, B, Sn, Nb, Ta, F) and higher temperatures of formation, which reflects the metamagmatic (fluid-magmatic) stage and is typical of the granites of the same kind in regions of "mature" continental crust. The obtained data are indicative of a long and universal process of granite formation. The degree of crust "maturity" is inferred from the composition of formed granitic rocks, their specific geochemistry, and the volumes occupied.
Keywords: Geochemistry; granitoids; batholith; modeling